Hubungan Pengetahuan Gizi dan Riwayat Pemberian ASI dengan Kejadian Stunting pada anak Balita: Hubungan Pengetahuan Gizi dan Riwayat Pemberian Air Susu Ibu dengan Kejadian Stunting pada Anak Balita - Emilia, Esi; Pratiwi, Caca; Akbar, Salsabila; Melayoga, Luqiyana (Amerta Nutrition, 2023)
Background: Nutritional knowledge in mothers is crucial in caring for toddlers. Providing nutrition has an impact on the growth and development of children. Breast milk contains complete nutrients. Exclusive breastfeeding for the first 6 months, followed by breastfeeding and complementary feeding, can prevent stunting. Objectives: This research aims to determine the correlation between maternal nutritional knowledge and history of breastfeeding with the occurrence of stunting in infants aged 24-59 months. Methods: The study was conducted in the working area of Angkup Community Health Center, Silinara District, Central Aceh. The study design was cross-sectional. A total sampling technique was used to select 38 toddlers. Data were collected using a questionnaire. The obtained results were analyzed using chi-square and multiple linear regression tests. Results: The analysis results showed an Asimp. Sig 0.020 < 0.05, indicating a significant association between maternal nutritional knowledge and the occurrence of stunting in toddlers. The analysis of breastfeeding also indicated an Asimp. Sig value of 0.004 < 0.05 suggests a significant association between breastfeeding and the occurrence of stunting in toddlers. Regression analysis demonstrated the influence of maternal nutritional knowledge and breastfeeding on the stunting variable by 35% in infants in the working area of Angkup Community Health Center, Central Aceh, from January to March 2022. Conclusions: The occurrence of stunting in the village of Angkup is related to maternal nutritional knowledge and the history of breastfeeding.